2007
DOI: 10.1016/j.ijsolstr.2006.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Design optimization for manufacturability of axisymmetric continuum structures using metamorphic development

Abstract: In this study, optimal shapes/profiles of axisymmetric continuum structures optimized for performance and manufacturability are sought, using a topology/shape optimization method called metamorphic development (MD). The optimization seeks to find an optimum cross-sectional profile and minimum weight design, subjected to von-Mises stress constraints under coupled thermal and pressure loadings. Both quadrilateral and triangular finite elements (FE) were used to 'metamorphically' develop the structure. Two differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 33 publications
0
7
0
1
Order By: Relevance
“…From a physical viewpoint, neither vertices of infinite curvature nor infinite stresses should exist. Sharp concave vertices can be eliminated though postoptimization by spline curve fitting and remeshing the newly created layout (Ngim et al, 2007). In this study, the optimized solution was retained, in order to facilitate the generation of an analysis model, and thereby investigate experimentally the performance of design solutions obtained directly by MD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From a physical viewpoint, neither vertices of infinite curvature nor infinite stresses should exist. Sharp concave vertices can be eliminated though postoptimization by spline curve fitting and remeshing the newly created layout (Ngim et al, 2007). In this study, the optimized solution was retained, in order to facilitate the generation of an analysis model, and thereby investigate experimentally the performance of design solutions obtained directly by MD.…”
Section: Discussionmentioning
confidence: 99%
“…The benefits of optimized structures are seldom realized, often due to geometric complexities, which restrict the necessary tooling access required by convectional subtractive-based manufacturing. Chang and Tang (2001) and Ngim et al (2007) demonstrated the design optimization for manufacturability, by collective technologies known as rapid manufacturing (RM), which offered the ability to produce optimized structures of virtually any geometric complexity (Wohlers, 2004). This current study was motivated by the applications of RM-based technologies, such as contour crafting (Khoshnevis, 2004) and freeform construction (Pegna, 1997;Buswell et al, 2007) which formed the basis of enabling technologies to address additive manufacturing solutions envisaged for future construction applications.…”
Section: Introductionmentioning
confidence: 99%
“…23 In these literatures about the optimization of disks, the optimal results tended to contain enclosed holes 19 which may challenge the manufacturing processes. 20 Besides, as observed in Rindi et al., 23 the optimal results tended to have indistinct solid-void interface.…”
Section: Introductionmentioning
confidence: 71%
“…17 The cooling channels in turbine blades were optimized in Ghosh et al. 18 Topology optimizations of turbomachinery disks were conducted in Shen et al., 19 Ngim et al., 20 Boccini et al., 21 , 22 and Rindi et al. 23 In these literatures about the optimization of disks, the optimal results tended to contain enclosed holes 19 which may challenge the manufacturing processes.…”
Section: Introductionmentioning
confidence: 99%
“…The present work aims at contributing to the filament path optimization of load-bearing FFF structures for maximizing their stiffness. A number of studies in the literature successfully employed optimization approaches to design AM parts with optimal topologies and mesostructures (Ngim et al (2007); Gaynor (2015); Zegard and Paulino (2016); Liu et al (2018)). Surprisingly, only a limited attention has been given to optimize the in-plane material placement in AM parts that is clearly advantageous for extrusionbased technologies (Tam and Mueller (2017), Zhang et al (2017)).…”
Section: Introductionmentioning
confidence: 99%